2018
DOI: 10.1007/s00427-018-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression characteristics and functional analysis of Krüppel-like factor 4 in adductor muscle and mantle of Zhikong scallop Chlamys farreri

Abstract: Krüppel-like factor 4 (KLF4) is an important transcription factor involving in formation and maintenance of muscles in mammals. However, no data are available on KLF4 function in shellfish muscles which play vital roles in the movement, stress response, and physiology in shellfish. In the present study, we revealed that the Klf4 mRNA of Zhikong scallop Chlamys farreri was expressed in most tissues, which has high level in adductor muscle, mantle, kidney, and testis. Positive signals of the Klf4 mRNA and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Both Wnt and β-catenin were downregulated at the proliferation and growth stages, and therefore we propose that B[a]P inhibited the oogenesis of C. farreri. Yang et al (2019) found that in C. farreri the Myc mRNA level increased gradually in the ovary along with gonadal development, and that a Myc-positive signal was located in oocytes at each stage; however, how Myc regulates gonad development and gametogenesis in the ovary remains unknown. The expression of Myc was significantly induced in the growth and mature stages of the ovary following B[a]P treatment, which promoted the proliferation of ovarian cells, but the mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Wnt and β-catenin were downregulated at the proliferation and growth stages, and therefore we propose that B[a]P inhibited the oogenesis of C. farreri. Yang et al (2019) found that in C. farreri the Myc mRNA level increased gradually in the ovary along with gonadal development, and that a Myc-positive signal was located in oocytes at each stage; however, how Myc regulates gonad development and gametogenesis in the ovary remains unknown. The expression of Myc was significantly induced in the growth and mature stages of the ovary following B[a]P treatment, which promoted the proliferation of ovarian cells, but the mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…We used β-actin as the reference gene because of its stable expression in previous experiments (Yang et al, 2020a). The primer for myelocytomatosis viral oncogene (Myc) was based on the research of Yang et al (2019). The genes we measured were obtained from the transcriptome of C. farreri, and the National Center for Biotechnology Information accession numbers are SPR238487 (gonads), SRP268573 (gonads), and SRP311574 (digestive glands).…”
Section: Real-time Qpcrmentioning
confidence: 99%